Jules Dassin's The naked city - Wald, Malvin; Rózsa, Miklós 1907-1995 (<<The>> Criterion Coll., 2007)
A squad of homicide detectives roam through the seamier parts of New York City as they solve a murder case. Gives viewers an unvarnished look at life in the city using the technique of neorealism.
Bildformat 1.33:1. - New, restored high-definition digital transfer
Orig.: USA 1948
Enth. audio commentary by "Naked city" screenwriter Malvin Wald ; a new video interview with NYU film professor Dana Polan ; an analysis of the film's New York locations by "Celluloid Skyline" author James Sanders ; footage of Jules Dassin from his 2004 appearance at the Los Angeles County Museum of Art ; stills gallery
Keywords: Detective and mystery films; Detectives -- New York (State) -- New York -- Drama; Feature films; Film noir; Murder -- Drama; Detektiv; Mord; Kriminalfilm; New York (N.Y.) -- Drama; New York, NY; Film; DVD-Video